(untitled) (Huellas, 2022)
Through an exercise of theoretical-interpretative analysis and the documentary and argumentative review of different biblio-hemerographic sources, the article intends to expose the main questions generated around the perspectives which have traditionally approached the subject of historical centers, in addition to showing the conceptual networks and the opening towards new approaches among which currently stands out the relational perspective. The objective is to rehearse one’s own theoretical formulating whose intention is to ascribe itself to this new current, since in various ways it approaches the understanding of the historic center as a social relationship. In this case the relational approach will be recovered from the field of geography and, in particular, from the theory of "the geometries of power" developed by Doreen Massey (2005). On this basis, in the end it is proposed that historical centers can be thought of as a dynamic and open simultaneity and product of interrelationships where different trajectories coexist currently, extending from the global to the local, which makes possible a trans-scalar visión, more complex and integral, which from the outset contributes to overcoming the traditional perspectives that usually conceive them as static and closed spaces, synonymous with "perimeter", "zone" or "area".